2021
DOI: 10.3390/land10101095
|View full text |Cite
|
Sign up to set email alerts
|

How Do Network Embeddedness and Environmental Awareness Affect Farmers’ Participation in Improving Rural Human Settlements?

Abstract: Based on social embeddedness theory, this paper aims to explore the influence mechanism of network embeddedness and environmental awareness on farmers’ participation in improving rural human settlements (IRHS). This research applies the Logit model and the Bootstrap method, using survey data from 495 farmers in Hubei Province, China. The results show that: (1) relational embeddedness has a significant negative impact on the centralized treatment of farmers’ domestic sewage, implying that strengthening the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…Research hypotheses H1 and H2 have been confirmed: the introverted communication and the extroverted communication constitute two different types of interactions of rural residents, and there is a trade-off relationship. Introverted communication has a positive and significant effect, which is consistent with the research results of Jinhua Xie et al [ 60 ]. Introverted communication is a communication activity carried out within a certain area.…”
Section: Discussionsupporting
confidence: 91%
“…Research hypotheses H1 and H2 have been confirmed: the introverted communication and the extroverted communication constitute two different types of interactions of rural residents, and there is a trade-off relationship. Introverted communication has a positive and significant effect, which is consistent with the research results of Jinhua Xie et al [ 60 ]. Introverted communication is a communication activity carried out within a certain area.…”
Section: Discussionsupporting
confidence: 91%
“…It was shown that social networks can increase rural residents' familiarity, reduce uncertainty in making behavioral decisions, and increase their level of domestic waste separation ( 49 51 ). In addition, the social network formed by the cadre-mass relationship can also enhance the flow and exchange of information and increase the level of trust among each other, thus promoting the participation of rural residents in rural environmental governance ( 52 ). Based on the above analysis, we propose the following hypothesis:…”
Section: Theoretical Hypothesismentioning
confidence: 99%
“…Therefore, it is of practical signi cance to place emphasis on the awareness of environmental protection, lifestyle, and health status of rural residents .Internationally, awareness of environmental protection refers to the extent to which individuals exhibit concern for the overall processes of the environment, possess an understanding of environmental issues and the quality of the environment, and demonstrate a commitment to environmental preservation in their daily lives (Yeung 1998). This awareness can be further categorized into three components: environmental cognition, environmental behavior, and environmental attitudes (Du et al 2018; Kousar et al 2022;Daghagh et al 2019;Liu et al 2020;Xie et al 2021). Recent research has indicated that awareness of environmental protection has the potential to in uence various aspects of rural residents' livelihoods and productivity (Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%